2016
DOI: 10.1093/brain/aww205
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer-related decrease in CYFIP2 links amyloid production to tau hyperphosphorylation and memory loss

Abstract: CYFIP2 is thought to regulate mRNA translation at synapses. Tiwari et al . reveal reduced CYFIP2 expression in post-mortem Alzheimer’s disease brains, and show that CYFIP2 reduction in mice causes abnormal amyloid production, tau hyperphosphorylation, and spatial memory loss. CYFIP2 could represent a molecular ‘hub’ with potential as a therapeutic target in Alzheimer’s disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 60 publications
(108 reference statements)
1
74
0
3
Order By: Relevance
“…Given that CYFIP2 is downregulated in post-mortem AD brain 22 , in a mouse model of AD 22 , and in primary cortical neurons following treatment with Aβ1-42 oligomers (Fig. 2i, j), we speculated that its reduction may be important in the pathogenesis of AD.…”
Section: Cyfip2 Reduction Leads To Age-dependent Accumulation Of Pre-mentioning
confidence: 99%
See 4 more Smart Citations
“…Given that CYFIP2 is downregulated in post-mortem AD brain 22 , in a mouse model of AD 22 , and in primary cortical neurons following treatment with Aβ1-42 oligomers (Fig. 2i, j), we speculated that its reduction may be important in the pathogenesis of AD.…”
Section: Cyfip2 Reduction Leads To Age-dependent Accumulation Of Pre-mentioning
confidence: 99%
“…Previously, we reported that 3-4 month old heterozygous Cyfip2 null mutants (Cyfip2 +/-), having about 50% reduced CYFIP2 expression, have increased levels of tau phosphorylation at Ser214, possibly due to a post-transcriptional increase in αCaMKII levels 22 . Here, we also found increased tau phosphorylation at Ser416, a αCaMKIIspecific phospho-site 40,41 , when normalised to levels of total tau ( Supplementary Fig.…”
Section: Cyfip2 Reduction Leads To Age-dependent Accumulation Of Pre-mentioning
confidence: 99%
See 3 more Smart Citations